خصائص فلسطين في القرآن الكريم - Mohanad Mustafa Abd Shat; Ahmad Kusjairi Suhail (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2022)
Throughout this study, the researcher aims to learn some Quranic verses related to Palestine and Jerusalem, historically showing their paramount importance and raising the awareness of Muslims for their roles in protecting the land from usurpers. The researcher attempted to do his best to mention all holy verses talk about Palestine. In this study, the researcher adopted the historical analytical method dependent on holy Qur’an verses, right Hadiths and ulema sayings. About the research itself, the researcher attempted to tackle desk-based research, counting on books, Arabic major sources, dictionaries and Arabic lexical structures and other related sources, Which are indispensable for the researcher to deal well with the different search axes. The conclusions drawn from this research include that Palestine is one of the oldest modern easternmost kingdoms of the cities and an integral part of the Levant. It enriches its importance due to its geographical location as an old-world crossroad between Asia, Europe and Africa. Also, it is a bridge that connects Arab countries. The research showed that man had inhabited Palestine since the Paleolithic period (500 thousand - 14 thousand BC. Allah Almighty proved that Palestine, Jerusalem, and surrounding areas are all blessed. Also, it has the divine good, like the provident of groundwater. Physically, Palestine and all surrounding areas are the garden of the Lord, sacred land and consecrated.